Penerapan Foot Care Education melalui Media Audiovisual untuk Meningkatkan Pengetahuan Pasien Diabetes Mellitus di Keluarga Binaan Puskesmas Sekaran Semarang - Diana Dayaningsih; Dwi Marliana (Inovasi Kesehatan Global, 2025)
The family is an essential unit consisting of two or more individuals living together due to ties of blood, marriage, or adoption, and it plays a significant role in supporting the health of its members, including those with diabetes mellitus, which can be hereditary. One of the serious complications that often arise in diabetes mellitus patients is diabetic ulcers, which can be prevented through proper foot care practices. In this context, the family has an important role in helping prevent foot injuries by providing support through foot care education. This study aims to describe the implementation of foot care education using audiovisual media as a means to improve the knowledge of diabetes mellitus patients in the working area of Sekaran Public Health Center, Semarang. The research method applied was a case study with a descriptive approach, in which an intervention was carried out through pre-test and post-test assessments related to foot care education using audiovisual media over five days, with the research instrument being the Diabetic Foot Knowledge Scale (DFKS) questionnaire. The results showed an increase in patient knowledge after the intervention, where in subject I the pre-test score was 8 (fair), which increased to 12 (good) in the post-test, while in subject II the pre-test score of 9 (fair) increased to 13 (good) in the post-test. These findings confirm that audiovisual-based foot care education is effective in enhancing the knowledge of diabetes mellitus patients regarding foot care. Based on the results, it is recommended that both patients and their families consistently apply foot care education in their daily activities, and health workers at Sekaran Public Health Center are encouraged to utilize audiovisual education methods as a strategy to improve patients’ knowledge and foot care practices, thereby preventing further complications in diabetes mellitus patients.